2020
DOI: 10.1073/pnas.1922370117
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin domain-containing 3 (Arrdc3) modulates insulin action and glucose metabolism in liver

Abstract: Insulin action in the liver is critical for glucose homeostasis through regulation of glycogen synthesis and glucose output. Arrestin domain-containing 3 (Arrdc3) is a member of the α-arrestin family previously linked to human obesity. Here, we show thatArrdc3is differentially regulated by insulin in vivo in mice undergoing euglycemic-hyperinsulinemic clamps, being highly up-regulated in liver and down-regulated in muscle and fat. Mice with liver-specific knockout (KO) of the insulin receptor (IR) have a 50% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…ARRDC3 deficiency in mice prevented age‐related obesity and increased insulin sensitivity [Patwari et al., 2011; Shea et al., 2012]. Also, liver‐specific ARRDC3 deletion increased hepatic insulin sensitivity, which was associated with increased insulin receptor protein levels, higher glycogen levels, and lower endogenous glucose production [Batista et al., 2020]. Mice with decreased ARRDC3 levels were protected from obesity due to increased energy expenditure.…”
Section: The Roles Of Other Arrdcs In Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…ARRDC3 deficiency in mice prevented age‐related obesity and increased insulin sensitivity [Patwari et al., 2011; Shea et al., 2012]. Also, liver‐specific ARRDC3 deletion increased hepatic insulin sensitivity, which was associated with increased insulin receptor protein levels, higher glycogen levels, and lower endogenous glucose production [Batista et al., 2020]. Mice with decreased ARRDC3 levels were protected from obesity due to increased energy expenditure.…”
Section: The Roles Of Other Arrdcs In Metabolismmentioning
confidence: 99%
“…Expression analyses showed that ARRDC3 is subjected to metabolic regulation in various tissues (adipose tissues or skeletal muscles) [Patwari et al., 2011; Batista et al., 2020], and both ARRDC2 and ARRDC3 expression are regulated by fasting/feeding in murine skeletal muscle [Gordon et al., 2019]. Co‐immunoprecipitation studies revealed that ARRDC3 interacts with the insulin receptor via its C‐terminal‐tail, which contains the PY motifs but also a tyrosine residue known to be phosphorylated in certain tumours [Batista et al., 2020]. How ARRDC3 influences insulin signalling mechanistically will require further studies, but current knowledge suggests that ARRDC3 is part of a negative feedback loop.…”
Section: The Roles Of Other Arrdcs In Metabolismmentioning
confidence: 99%
“…In addition to signalling through canonical substrates and downstream elements, the insulin receptor and its signalling are also regulated, both positively and negatively, by interaction with membrane and intracellular proteins. These include glycosylphosphatidylinositol (GPI)-linked proteins, such as glypican-4 [18], membrane pyrophosphatases and phosphodiesterases, such as ectonucleotide pyrophosphatase/ phosphodiesterase 1 (PC-1) [19], α-arrestin adaptors [20] and, even, transcription factors [21] and cell-cycle regulators [22].…”
Section: Defining the Insulin Signalling Networkmentioning
confidence: 99%
“…Figure 2C-D) in LivARKO-DHT compared to Con-DHT mice. HGP is not uncommon to have it negative[41,42] as far as insulin suppression of HGP is significantly greater in LivARKO-DHT compared to Con-DHT. Hormones and metabolites commonly associated with insulin resistance and obesity (i.e., leptin, IL-6, and tumor necrosis factor-α) showed similar patterns among Con-veh, LivARKO-veh, Con-DHT, and LivARKO-DHT mice (Figure 3C-E).…”
Section: Resultsmentioning
confidence: 99%